ANALYSIS OF THE CRIMINAL NON-PROSECUTION AGREEMENT FROM THE CONSTITUTIONAL PRISM (REMUNOM, 2024)
The non-criminal prosecution agreement was introduced into the Brazilian legal system through Law 13,964/19, as a consensual method of resolving conflicts. However, the aforementioned institute brought difficulties linked to its execution, since when it was established there was a transgression of constitutional guarantees. Therefore, this work deals with the application of constitutional principles in the necessary requirements for offering a non-criminal prosecution agreement. Thus, through bibliographical research and study of applied legislation, it was found that despite being a promising institute, some requirements of the institute under analysis are in line with constitutional principles, as well as fundamental rights.